(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Losartan potassium is used as an antihypertensive drug but it goes under first pass metabolism due do which it has low bioavailability. Fast onset of action is major concern in the management of hypertension. Therefore the aim of this study is to formulate mouth dissolving tablet of losartan potassium to improve its bioavailability, to achieve fast onset of action and increase patient compliance. Mouth dissolving tablets were prepared by direct compression method using natural super disintegrating agents (banana powder & apple pectin) and evaluated for pre-compression parameters and post compression parameters such as appearance, dimensions, hardness, weight variation, friability, wetting time, dispersion time, water absorption ratio, disintegration & dissolution study. According to results of optimized batches it has been concluded that formulation batch F9 was an ideal batch which contain banana powder (2.5%) & cross povidone (2.5%) showed least disintegration time that is 26 seconds & maximum drug release of (99.68%) within 12 minutes and was best among all the formulations.